Human powered LED torches - Ahmad Zarir, Mohamad (2007)
This project’s purpose is to make the torches that can operate in two modes which are based on mechanical source (using stepper motor) and battery source. User can choose which mode they wanted to. This project is modifications from the existed product exist in the market. These human-powered LED torches have some really good emergency applications. WE can use this torch whenever we out of battery. The objective of this project is to produce a torchlight which can operate without or with battery. To save energy used by using mechanical application. For part 1 which is, this project just need a basic component to operate first is stepper motor which generates the power to run thing, second is rectifier which to converts AC to DC and capacitor which is to store the power and finally the LED itself to produce lights. Part 2 is a low battery detector circuit which is detect and sound an alarm when battery is low. And lastly is part 3, DC charging circuit, whereas to charging the battery. As a result, LEDs will produce a light by those two modes and user can choose which one they need. This project will give a benefit to user in any way whether mechanical part or using battery mode part.